Efficacy of Combined General, Special, and Specific Resistance Training on Pace Bowling Skill in Club-Standard Cricketers. Issue 9 (September 2020) - Feros, Simon A.; Young, Warren B.; O'Brien, Brendan J.
Abstract : Abstract: Feros, SA, Young, WB, and O'Brien, BJ. Efficacy of combined general, special, and specific resistance training on pace bowling skill in club-standard cricketers. J Strength Cond Res 34(9): 2596–2607, 2020—This study investigated the efficacy of combined "general, " "special, " and "specific" resistance training on pace bowling skill. Twelve male, club-standard pace bowlers were randomly allocated to a combined resistance training (CRT) program or traditional cricket training (TCT) program for 8 weeks. The CRT group ( n = 6) trained with 300, 250-g, and standard cricket balls; performed 20-m sprints with +20% and +15% body mass resistance (but also unresisted); and completed chin-up and pull-up training. The TCT group ( n = 6) trained with standard balls and performed unresisted 20-m sprints. No statistically significant GROUP × TIME interactions were identified. The CRT group demonstrated a "clear moderate" enhancement in peak ball release speed (mean ±95% confidence limits [CLs]: 1.2 ± 1.5 m·s −1, d = 0.66 ± 0.83), a "clear large" increase in mean radial error (mean ±95% CLs: 7.1 ± 6.5 cm, d = 0.94 ± 0.87), and a "clear large" rise in bivariate variable error (mean ±95% CLs: 7.2 ± 7.8 cm, d = 0.97 ± 1.05). The TCT group exhibited "unclear" changes across all pace bowling skill measures. Both groups displayed "unclear" changes in approach speed, 20-m sprint time, and 1 repetition maximum pull-up strength. In 8 weeks, the CRT program improved peak ball release speed, but at the cost of poorer bowling accuracy and consistency of bowling accuracy. These findings could be attributed to bowling with the heavier balls. The inclusion of "specific" resistance training does not seem to be effective in enhancing all-round pace bowling skill in club-standard cricketers.